2020
DOI: 10.1016/s2352-4642(19)30323-2
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in insufficient physical activity among adolescents: a pooled analysis of 298 population-based surveys with 1·6 million participants

Abstract: SummaryBackgroundPhysical activity has many health benefits for young people. In 2018, WHO launched More Active People for a Healthier World, a new global action on physical activity, including new targets of a 15% relative reduction of global prevalence of insufficient physical activity by 2030 among adolescents and adults. We describe current prevalence and trends of insufficient physical activity among school-going adolescents aged 11–17 years by country, region, and globally.MethodsWe did a pooled analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

96
1,598
18
131

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,141 publications
(2,156 citation statements)
references
References 23 publications
96
1,598
18
131
Order By: Relevance
“…Worryingly, a recent systematic review identified that there is insufficient evidence to allow for firm conclusions to be made regarding the impact of PA interventions on inequalities [53]. According to the WHO, effective national action to reduce disparities in PA requires a strategic combination of population-based policy actions aimed at tackling the "upstream" determinants that shape the equity of opportunities for participation (such as encouraging nonmotorised modes of travel through improved provision of cycling and walking infrastructure, improved road safety, and creating more opportunities for PA in public open spaces and local community settings [54]) and those policy actions that are focused on "downstream" individually-focused (educational and informational) interventions, implemented in ways consistent with the principle of proportional universality (i.e. greatest efforts directed towards those least active) [55].…”
Section: Implications For Policymentioning
confidence: 99%
“…Worryingly, a recent systematic review identified that there is insufficient evidence to allow for firm conclusions to be made regarding the impact of PA interventions on inequalities [53]. According to the WHO, effective national action to reduce disparities in PA requires a strategic combination of population-based policy actions aimed at tackling the "upstream" determinants that shape the equity of opportunities for participation (such as encouraging nonmotorised modes of travel through improved provision of cycling and walking infrastructure, improved road safety, and creating more opportunities for PA in public open spaces and local community settings [54]) and those policy actions that are focused on "downstream" individually-focused (educational and informational) interventions, implemented in ways consistent with the principle of proportional universality (i.e. greatest efforts directed towards those least active) [55].…”
Section: Implications For Policymentioning
confidence: 99%
“…Globally, 50% of children do not meet the internationally recognised target of 60 min of moderate-to-vigorous physical activity (MVPA) per day [1,2]. This figure rises to 80% in higher-income countries [2] and persists into adolescence [3]. Given these figures, it is not surprising that the latest global physical activity report card states "children's physical activity poses a serious level of concern" [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO 2010 physical activity recommendations, school‐aged children should participate daily in at least 60 minutes of moderate to vigorous physical activity (MVPA) 1 . However, as shown in recent global data with questionnaire and accelerometer measurements, less than one third of the underage population 2 and one fifth of adolescents comply with this recommendation 3 . Most of the recent studies in which physical activity (PA) has been measured with accelerometers agree that the decline in PA begins around the time of school entry and continues through adolescence 4 .…”
Section: Introductionmentioning
confidence: 99%